Computerized Three-Dimensional Pedicle Morphometry From Computed Tomography Images of the Thoracic Spine - Knez, Dejan; Vrtovec, Tomaž (Image Analysis and Stereology, 2020)
Knowledge of pedicle morphometry is valuable for a safe and reliable pedicle screw placement. In this study, we performed and evaluated computerized pedicle morphometry measurements from preoperative computed tomography (CT) images of the thoracic spine from 26 subjects. Manual measurements of the pedicle width, height and chord length were obtained for 540 thoracic pedicles in selected cross sections of orthogonal and oblique multiplanar reconstructions (MPRs). Computerized measurements of the pedicle width, height, length, chord length, transverse angulation, sagittal angulation and cross-sectional area were obtained for the same pedicles by an automated method that is based on parametric modeling of vertebral structures in three dimensions (3D). Statistical analysis revealed that manual measurements from orthogonal MPRs were significantly different (p ≤ 1.1·10−3) when compared to those from oblique MPRs and computerized measurement in 3D, with the respective mean absolute difference (MAD) ± standard deviation (SD) of 0.77 ± 0.56 mm and 0.74 ± 0.57 mm for the pedicle width, and 1.31 ± 1.08 mm and 1.45 ± 1.10 mm for the pedicle height. No statistically significant differences (p ≥ 0.12) were observed between manual measurements from oblique MPRs and computerized measurements in 3D, with MAD ± SD of 0.44 ± 0.35 mm, 0.56 ± 0.52 mm and 1.72 ± 1.29 mm for the pedicle width, height and chord length, respectively. The advantage of computerized measurements is that they allow the extraction of additional pedicle morphometric parameters, which are important for preoperative planning of pedicle screw placement, or can be used for population and demographic studies using larger pedicle databases.